2017
DOI: 10.1186/s12870-017-1204-2
|View full text |Cite
|
Sign up to set email alerts
|

De novo assembly and comparative analysis of the transcriptome of embryogenic callus formation in bread wheat (Triticum aestivum L.)

Abstract: BackgroundDuring asexual reproduction the embryogenic callus can differentiate into a new plantlet, offering great potential for fostering in vitro culture efficiency in plants. The immature embryos (IMEs) of wheat (Triticum aestivum L.) are more easily able to generate embryogenic callus than mature embryos (MEs). To understand the molecular process of embryogenic callus formation in wheat, de novo transcriptome sequencing was used to generate transcriptome sequences from calli derived from IMEs and MEs after… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
35
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(35 citation statements)
references
References 97 publications
0
35
0
Order By: Relevance
“…We have established an e cient rubber tree SE system using immature anthers. The transcriptome analysis of plant SE revealed a large number of potential key factors of embryogenesis [25,26,[44][45][46]. In this study, we obtained the transcriptome analysis of rubber tree SE derived from EC, PE, CE, AE, MCE and WAE.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We have established an e cient rubber tree SE system using immature anthers. The transcriptome analysis of plant SE revealed a large number of potential key factors of embryogenesis [25,26,[44][45][46]. In this study, we obtained the transcriptome analysis of rubber tree SE derived from EC, PE, CE, AE, MCE and WAE.…”
Section: Discussionmentioning
confidence: 99%
“…The WRKY genes showed higher expression and be related to embryogenic callus formation [82]. The up-regulated WRKY genes were high ratio in embryogenic callus formation of bread wheat [44]. In addition, MYB family was also involved in plant development and growth [83][84][85][86], hormone signal transduction [87,88].…”
Section: Discussionmentioning
confidence: 99%
“…As a functional molecular marker, SSRs generated from expressed sequence tags (EST-SSRs) can investigate the effects of environmental heterogeneity and local adaptation due to its tight linkage with functional genes controlling phenotype [20][21][22]. Up till now numbers of EST-SSRs developed and checked for polymorphism in many species, such as sweet potato [23], Sesamum indicum [24], radish [25], Cymbidium sinense [26], Chinese bayberry [27], Silver r [28], Salix, Populus, Eucalyptus [29]; Rosa roxburghii [30], Neottopteris nidus [16], Lacquar tree [31], Bread wheat [32], Proso Millet [33], Almond [34] and Ginseng [35]. Limited genomic resources have been developed for Panax species so far, e.g., P. vietnamensis var.…”
Section: Introductionmentioning
confidence: 99%
“…The molecular mechanisms that orchestrate somatic embryogenesis and endow biological totipotency are becoming better understood [28]. Previous studies have shown that genes expressed during the induction of SE can be divided into three primary categories; stress-related genes, plant growth regulator (PGR) related genes, and transcription factors [29][30][31]. A biological stress, such as senescence or an acute stress such as abiotic/biotic factors can trigger stem cell formation through altered chromatin conformation and promiscuous expression of transcription factors [32][33][34].…”
Section: Introductionmentioning
confidence: 99%